2014
DOI: 10.1002/anie.201402653
|View full text |Cite
|
Sign up to set email alerts
|

A Smart Library of Epoxide Hydrolase Variants and the Top Hits for Synthesis of (S)‐β‐Blocker Precursors

Abstract: Microtuning of the enzyme active pocket has led to a smart library of epoxide hydrolase variants with an expanded substrate spectrum covering a series of typical β-blocker precursors. Improved activities of 6- to 430-fold were achieved by redesigning the active site at two predicted hot spots. This study represents a breakthrough in protein engineering of epoxide hydrolases and resulted in enhanced activity toward bulky substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 30 publications
(6 reference statements)
1
26
0
Order By: Relevance
“…Of special relevance is conformational state 3 F128A , not observed in the wild‐type enzyme, that presents a wide active site pocket ready to bind NGE and facilitate the product release. The partial unfolding of Tyr144 α‐helix observed in our MD simulations is in line with the experimental observation that doubly mutated F128S/M145S variant presents severe protein folding problems . To further evaluate our hypothesis, we decided to computationally evaluate the M145S variant.…”
Section: Figuresupporting
confidence: 78%
See 1 more Smart Citation
“…Of special relevance is conformational state 3 F128A , not observed in the wild‐type enzyme, that presents a wide active site pocket ready to bind NGE and facilitate the product release. The partial unfolding of Tyr144 α‐helix observed in our MD simulations is in line with the experimental observation that doubly mutated F128S/M145S variant presents severe protein folding problems . To further evaluate our hypothesis, we decided to computationally evaluate the M145S variant.…”
Section: Figuresupporting
confidence: 78%
“…Alanine scanning experiments at two positions located in the substrate entrance and product release zones, for example, residues F128 and M145, were used to support the hypothesis of the different active site tunnels . Interestingly, mutation of both positions to smaller residues (serine and alanine) was found to be crucial for enhancing the catalytic activity of the enzyme towards the resolution of bulky epoxide substrates such as naphthyl glycidyl ether ( NGE , the activity is from 25 to 434 times higher than for the wild‐type enzyme) ,. This increase in activity was attributed to the wider product release zone 3 of the variants that is supposed to facilitate the product dissociation step …”
Section: Figurementioning
confidence: 99%
“…Moreover, we can carry out gram-scale synthesis of (S)-propranolol with the M145A variant of BmEH. Further studies to generate an EH library by semisaturation mutations on the identified hot spots has broadened the substrate scope to more drug precursors in our laboratory (29).…”
Section: Discussionmentioning
confidence: 99%
“…The rotation and translation functions were calculated at 2.5 A resolution. All potential space groups were checked for with the solution being found in P6 5 . The rotation solution peak height was 3.8 r and the translation solution peak was 5.6 r. The resulting MR solution was subjected to restrained refinement in REFMAC5 [34] resulting in an R-factor of 40.3% and an R-free of 43.2% after 30 cycles of refinement.…”
Section: Data Collection and Structure Determinationmentioning
confidence: 99%
“…chiral precursors of b-blockers [4,5]. These cofactor-independent enzymes can be applied in enantioselective kinetic resolution processes of racemic epoxides as well as in the stereoselective hydrolysis of meso-epoxides, in many cases with high selectivity and conversion yields [6].…”
Section: Introductionmentioning
confidence: 99%